Maintenance du lexique-grammaire: Formules définitoires et arbre de classement - Tolone, Elsa (2011)
Lexicon-Grammar tables, whose development was initiated by (Gross, 1975), are a very rich syntactic lexicon for the French language. This paper presents the work done to formalize the existing classification of verbs using logical formulas, in order to maintain the lexicon. We describe the different types of definitional features and their coding in the table of classes, which is composed by all the features of all classes of verbs. The formal definition of all the defining features for each class has to consider the classification with a decision tree to help finding the class associated with a new entry, which ensures the future extension of the lexicon.